The Effect of Entrepreneurship Training and Islamic Entrepreneurship Knowledge on Entrepreneurial Interest - Hasan Abdurrahim; Fajar Surya Ari Anggara (University of Darussalam Gontor, 2020)
Unemployment at the level of tertiary graduates increases in 2019. Entrepreneurship training is expected to increase students' interest in entrepreneurship for the sake of creating broad jobs. Besides, entrepreneurial knowledge also plays an important role related to entrepreneurial inte rests. Therefore, in this study aims to determine the effect of entrepreneurship training and Islamic entrepreneurship knowledge on entrepreneurial interest. The research used was quantitative research with survey research methods. Sampling using simple random sampling from 155 students from a total population of 271 students in three different study programs that are members of the IEBC program, namely Islamic economics, management, and informatics engineering courses. (IEBC) is an intensive training program organized in a conducive Pesantren university education environment. Based on the results of the study, there is a positive and significant effect on entrepreneurship training and entrepreneurial knowledge on entrepreneurial interest with the results of multiple linear regression tests. The result of this research indicates that the higher the entrepreneurship training and Islamic entrepreneurship knowledge, the higher the interest in entrepreneurship. From this research, it can be concluded that the Islamic Entrepreneur Bootcamp should better equip students or participants with entrepreneurship training and Islamic entrepreneurship knowledge to increase the interest of entrepreneurial students. This study also suggests the next researcher applies the research to a broader object.